Enhancing Antioxidant Activity of Curcumin Using ZnO Nanoparticles Synthesized by Electrodeposition Method - Nisrina Fitri Nur Syamsi fitri; Alsifa Andita Putri; Rachmaniah Nurul Imani; Suci Putriyaningsih; Devia Alventiana Sipayung; Anis Sakinah (Chemistry and Materials, 2023)
The objective of this study was to fabricate zinc oxide (ZnO) nanoparticles through the utilization of the electrodeposition technique, to employ them as a supportive medium for enhancing the antioxidant properties of curcumin. The study involved the synthesis of ZnO nanoparticles, which were subsequently subjected to characterization using X-ray diffraction (XRD), scanning electron microscopy (SEM), and electrochemical impedance spectroscopy (EIS). Additionally, the antioxidant activity of the synthesized nanoparticles was assessed through the use of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. In XRD analysis, a notable peak denoted by an asterisk (*) is observed at specific angles of 2θ: 25.84°, 31.63°, 34.21°, and 36.12°, with corresponding index values (h, k, l) of (220), (100), (002), and (101), respectively. This peak is indicative of the degree of crystallinity exhibited by ZnO nanoparticles. The SEM data indicates that the particles generated possess a rod-like morphology, exhibiting a range of sizes. The Nyquist plots exhibit a semicircular arc pattern at low frequencies, as indicated by the findings from the EIS test. The data obtained from antioxidant assays indicated that ZnO-curcumin achieved an inhibition level of 47.09%, while curcumin alone showed a significantly lower inhibition percentage of 4.93%.